Pretreatment of lignocellulosic biomass by Fenton-like reaction (catalyzed by superparamagnetic Fe-NPs) combined with fungal MnP enzyme. - Hermosilla - Carrasco; Edward (2023)
2 GOAL 2. To evaluate the effect of MnP enzyme on wheat straw pretreatment for increasing enzymatic hydrolysis. TOTAL The study aimed to optimize the use of the white-rot fungus Anthracophyllum discolor to produce a concentrated extract high in manganese-peroxidase (MnP) activity (3478 U/L) for the pretreatment of wheat straw. Using a surface response experimental design, optimal pretreatment conditions for Mn2+, H2O2, pH, and MnP loading were determined to maximize glucose yield during enzymatic hydrolysis. The resulting optimal conditions were 4 mM Mn2+, 2 mM H2O2, pH 4.2, and 23 U g-1 MnP, resulting in a 46% glucose yield, 2.27 times higher than untreated wheat straw. The pretreatment caused 30% lignin degradation and structural changes observed by electronic microscopy, which can improve the action of commercial cellulases. The best results were obtained at a solid loading of 5% w/v wheat straw, with decreasing glucose yield of 21% and 24% at higher solid loadings of 7.5% and 10%. Therefore, goal 2 was fulfilled 100%. 3 GOAL 3. To evaluate the effect of fungal peroxidase enzymes combined with a Fenton-like reaction (catalyzed with Fe-NPs) on the pretreatment of wheat straw for increasing enzymatic hydrolysis. TOTAL The study aimed to evaluate the impact of using iron nanoparticles (SP Fe-NPs) in alginate beads on the manganese-peroxidase (MnP) activity in a simultaneous pretreatment with the white-rot fungus Anthracophyllum discolor. The results showed a decrease of 73% in MnP activity and impractical H2O2 concentration for simultaneous pretreatments. The study also investigated the effect of sequential pretreatments using Fenton-like followed by MnP enzyme or MnP enzyme followed by Fenton-like on the enzymatic hydrolysis of wheat straw. The results showed a synergistic effect when Fenton-like was followed by MnP enzyme resulting in 65.9% glucose yield and 35.2% lignin degradation. A lower glucose yield of 60.3% was obtained when the MnP enzyme was followed by Fenton-like. Therefore, goal 3 was fulfilled ...